2021
DOI: 10.1111/jir.12879
|View full text |Cite
|
Sign up to set email alerts
|

Updated profiles of everyday executive function in youth with Down syndrome using the BRIEF‐2

Abstract: Background Executive function difficulties in youth with Down syndrome (DS) are well recognised using informant-report measures. However, the profile of relative challenges and strengths has not yet been evaluated using the Behavior Rating Inventory of Executive Function, Second Edition (BRIEF-2), which includes a new internal factor structure. Method Using the BRIEF-2, profiles of everyday parent-reported executive function (EF) were evaluated in youth with DS (n = 34) and compared with age-based and sex-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Moreover, the group-level profile seems to partially vary by factors like age and environmental context. Preschool and school-age children varied somewhat in their EF profiles in the Onnivello et al (2022) study, and greater EF challenges were reported by teachers relative to parents in the Csumitta et al (2022) study. These and other similar dimensions are important to consider when describing syndrome-related performances on the group level.…”
Section: Aetiology-specific Findingsmentioning
confidence: 92%
See 4 more Smart Citations
“…Moreover, the group-level profile seems to partially vary by factors like age and environmental context. Preschool and school-age children varied somewhat in their EF profiles in the Onnivello et al (2022) study, and greater EF challenges were reported by teachers relative to parents in the Csumitta et al (2022) study. These and other similar dimensions are important to consider when describing syndrome-related performances on the group level.…”
Section: Aetiology-specific Findingsmentioning
confidence: 92%
“…Also, several papers in this special issue reach the conclusion that proxy‐report measures used to assess EF in the general population, such as the BRIEF and its different forms, might are sensitive tools for identifying difficulties and profiles at least for some specific ID aetiologies such as Down and Williams syndrome (Csumitta et al . 2022; Greiner de Magalhaes et al ., 2022; Onnivello et al . 2022).…”
Section: Methodological Issuesmentioning
confidence: 99%
See 3 more Smart Citations